Metastasis Suppressor NME1 Directly Activates Transcription of the ALDOC Gene in Melanoma Cells - PAMIDIMUKKALA, NIDHI V. (Anticancer Res, 2018)
BACKGROUND/AIM: NME/NM23 nucleoside dipho-sphate kinase 1 (NME1) is a metastasis suppressor gene, exhibiting reduced expression in metastatic cancers and the ability to suppress metastatic activity of cancer cells. We previously identified NME1-regulated genes with prognostic value in human melanoma. This study was conducted in melanoma cell lines aiming to elucidate the mechanism through which NME regulates one of these genes, aldolase C (ALDOC). MATERIALS AND METHODS: ALDOC mRNA and protein expression was measured using qRT-PCR and immunoblot analyses. Promoter-luciferase constructs and chromatin immunoprecipitation were employed to measure the impact of NME1 on ALDOC transcription. RESULTS: NME1 enhanced ALDOC transcription, evidenced by increased expression of ALDOC pre-mRNA and activity of an ALDOC promoter-luciferase module. NME1 was detected at the ALDOC promoter, and forced NME1 expression resulted in enhanced occupancy of the promoter by NME1, increased presence of epigenetic activation markers (H3K4me3 and H3K27ac), and recruitment of RNA polymerase II. CONCLUSION: This is the first study to indicate that NME1 induces transcription through its direct binding to the promoter region of a target gene.